Tunicamycin Induces Hepatic Stellate Cell Apoptosis Through Calpain-2/Ca2 +-Dependent Endoplasmic Reticulum Stress Pathway - Liu, Haiying; Dai, Linyu; Wang, Ming; Feng, Fumin; Xiao, Yonghong (Frontiers in Cell and Developmental Biology, 2021)
It has been reported that calpain/caspase mediated apoptosis induced by endoplasmic reticulum stress (ERS) in hepatic stellate cells (HSCs) by previous studies. At present, the activation of hepatic stellate cell is an important cause of liver fibrosis, and the induction of hepatic stellate cell apoptosis plays an irreplaceable role in reversing liver fibrosis. Therefore, it is of great significance to explore mechanisms of action that can induce hepatic stellate cell apoptosis for the reversal of hepatic fibrosis and the clinical prevention and treatment of hepatic fibrosis related diseases such as hepatitis, cirrhosis and liver cancer. In the current study, we demonstrated that tunicamycin (a novel endoplasmic reticulum stress inducer) can induce the apoptosis of HSCs, increase the concentration of intracellular Ca2+ and the expression of ERS protein GRP78, apoptosis protein caspase-12 and Bax, while decrease the anti-apoptosis protein expression of Bcl-2. Our findings indicate that tunicamycin can induce HSCs apoptosis through calpain-2/Ca2+ dependent endoplasmic reticulum stress pathway.